Memory, myth and modernism in Kazuo Ishiguro`s "The Buried Giant" - Gołębiowska, Urszula; Kubasiewicz, Mirosława (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Kazuo Ishiguro`s affinities with modernism have been the subject of critical studies of his earlier works, which have been found to display such modernist features as the preoccupation with psychological and moral depth and the exploration of the inner life. Correspondences with modernizm are also detectable in his most recent novel, "The Buried Giant" (2015).
Keywords: modernism; collective memory; individual memory; forgetting; involuntary memory; myth; Ishiguro, Kazuo (1954- )